Genetic Variation in Wood Fiber Length in Poplar (Populus deltoides Bartr.) - Dhillon, G.P.S.; Sidhu, D.S.; Singh, Avtar (Indian Journal of Agroforestry, 2020)
Wood fiber length of thirty seven clones of poplar (Populus deltoides Bartr.) was measured from the samples collected at breast height level. Poplar clones were grown at two locations of Punjab viz. central plain region (Ludhiana) and semi-arid region (Bathinda). Significant differences among clones were noticed at both locations. Fiber length ranged from 0.946 to 1.105 mm in central plain region and from 0.964 to 1.236 mm in semi-arid region. The promising clones in central-plain region and semi-arid region were 421-2, 82-26-5 and L-62/84, and RD-01, 26-N, S7C20, ST-124, 38-N and 40-N, respectively. The pooled analysis revealed significant clonal and location differences. Clones RD-01, 421-2, S7C20 and ST-124 registered significantly higher fiber length than control (0.997 mm). The genotypic and phenotypic coefficients of variation were low (1.99 to 5.32%). The heritability was moderate (22.37%) in central plain region and high (69.57%) in semi-arid region. Selection of promising clones for end use of wood on basis of fiber length has been discussed.